Comparação de técnicas coproparasitológicas para o diagnóstico de protozoários e helmintos intestinais de importância médica - Ribeiro, Steveen Rios (2011)
Introduction. The diagnosis of intestinal parasites can be accomplished by different techniques of parasitological stool examinations (EPF), each with advantages and disadvantages according to the parasite to be identified. Aims. The aim of the present study was to compare traditional techniques of EPF (Spontaneous Sedimentation in Tube, Kato-Katz and Baermann-Moraes) with more sophisticated techniques (stool culture, detection of coproantigen and PCR) and two commercially available kits in Brazil (Paratest® and TF-Test ®). Material and Methods. Faecal samples from 160 individuals, a total of 356 samples, were analyzed by traditional techniques of EPF (Spontaneous Sedimentation in Tube, Kato-Katz and Baermann-Moraes), culture of fresh faeces and sediment of feces, detection of coproantigen, PCR for detection and differentiation of the complex Entamoeba histolytica/Entamoeba dispar and two commercially available kits in Brazil (Paratest® and TF-Test®). Results. The technique of Spontaneous Sedimentation in Tube had better sensitivity (80.43% of occurrences) for the diagnosis of eggs and larvae of helminths in feces. The Kato-Katz was better for identification of eggs of S. mansoni (100% of cases). The method of Baermann-Moraes found larvae of Strongyloides stercoralis detected similarly to spontaneous sedimentation. For the diagnosis of G. lamblia, C. parvum and E. histolytica, kits for detection of coproantigen showed better sensitivity. The stool culture showed excellent results for identification of Blastocystis hominis. The PCR was able to identify and differentiate the amoebas of the complex E. histolytica/ E. dispar. Both commercial kits showed lower sensitivity than the spontaneous sedimentation for the diagnosis of helminths, but Paratest® was the technique that has shown better sensitivity for protozoa (66.66% of cases). Conclusion. For the diagnosis of helminths, the Spontaneous Sedimentation Method in Tube showed better results, except for detection of eggs of S. mansoni, best detected by Kato-Katz. For the diagnosis of G. lamblia, E. histolytica and Cryptosporidium parvum, kits for detection of coproantigen were better. However, the kit for the diagnosis of E. histolytica does not detect the species E. dispar, best identified by the ABSTRACT PCR. The commercial kits (Paratest® and TF-Test ®), while facilitating the collection and preservation of the sample, have lower sensitivity than the Spontaneous Sedimentation method in Tube